THE EFFECT OF DIABETES GYMNASTIC ON ANKLE BRACHIAL INDEX (ABI) VALUE IN PATIENTS WITH DIABETES MELLITUS - Kaimuddin Kaimuddin; Selamat Selamat (Poltekkes Kemenkes Jambi, 2019)
Background: The increased number of diabetic patients is related to lifestyle, high obesity prevalence and lack of physical activity. One of the complication for diabetic patients is diabetic foot caused by peripheral vascularization disorders which can be measured by the value of the Ankle Brachial Index (ABI). The purpose of this study was to determine the effect of diabetes exercises on ABI value in patients with diabetes mellitus. Methods: This research was conducted quantitatively with a quasi-experimental with pre-post control group design. This research was conducted in the gymnastics diabetes group in Health center of Simpang IV Sipin Kota Jambi using primary data. Participants in this study were 70 members of DM gymnastics. To reduce the research bias between the intervention group and the control group, matching was done based on age, sex, body mass index, and smoking habits, so as to get 30 participants which divided into 2 groups, intervention and control group with a ratio of 1: 1. Data analysed using independent t test. Results: The Ankle Brachial Index (ABI) mean value of the intervention group was 1.204 with median of 1.209. While the ABI mean value of the control group was 1.152 with median of 1.155. Independent t-test (Unpaired) showed a significant difference of ABI value (p-value 0.013) between after given the exercise treatment in the treatment group and in the control group. Conclusion: There is an influence between the application of diabetes exercises in the changes of the ABI value in patients with DM. It is suggested if the frequency of exercise becomes 3 times / week to gain a better impact for the diabetics patient.